Change of Strategic Management Paradigm in the Context of Knowledge Economy - Lytovchenko, Bohdan (TNEU, 2009)
In the article the questions of evolution of theory and practice of management are examined concerning nature of role of man in an economy. The basic stages of development of strategic management are analysed in the context of changes of organizational culture. The questions of mutual impact of management and economic theory in directions of modern of scientific thought are aolso revealed.
Keywords: Human capital; human factor; management of human capitals; management of a man